TECHNOLOGICAL ASPECTS OF PRESERVATION PROCESSIG Of EDIBlE SHELL FISHES III..FACTORS INFLUENCING THE KEEPING QUALITY OF CRAB (SCYLLA SERRATA) DURING FREEZING AND FROZEN STORAGE - GEORGE, CHINNAMA GEORGE (Fishery Technology, 2016)
The possible factors leading to the loss of flavour and general quality of crab during freezing and frozen storage have been studied. The preprocess ice storage condition of the raw material was found to be one such important factor while the fresh frozen crab meat remained in good organoleptic condition for about 51 weeks at -23Â°C, the 7 days iced material held frozen was found to have a shelflife of about 21 weeks. The fall in myofibrillar protein noted during frozen storage together with the loss of myosin ATPase activity correlated well with the loss of organoleptic qualities.